Hubungan Kinerja Penyuluh Pertanian Lapangan Terhadap Kepuasan Petani Kopi Robusta: Di Desa Kemiri Kabupaten Jember - Widjayanthi, Lenny; Lutfiah, Diana (Fakultas Pertanian, Universitas Lampung, 2025)
Kemiri Village is one of the villages in Panti Subdistrict, Jember Regency, with the highest potential for robusta coffee production in Panti Subdistrict. The number of Field Agricultural Extension Workers (PPL) in Kemiri Village, Panti Subdistrict, Jember Regency is limited to only one PPL. This PPL serves two villages, namely Kemiri Village and Suci Village, and handles all commodities of food crops, horticulture, and plantations. This situation can lead to suboptimal performance of the extension worker. The objectives of this research are to: 1) determine the performance level of Field Agricultural Extension Workers (PPL) in Kemiri Village, Panti Subdistrict, Jember Regency based on the performance indicators of Field Agricultural Extension Workers (PPL); 2) determine the satisfaction level of robusta coffee farmers with the performance of Field Agricultural Extension Workers (PPL) in Kemiri Village, Panti Subdistrict, Jember Regency; and 3) determine the relationship between the performance of Field Agricultural Extension Workers (PPL) and the satisfaction of robusta coffee farmers in Kemiri Village, Panti Subdistrict. The location of the research was determined using a purposive method. The research method used was descriptive-analytic with a quantitative approach. The sampling method used was total sampling and proportionate stratified random sampling. The results of the study showed that: 1) The performance level of agricultural extension workers in Kemiri Village, Panti Subdistrict, Jember Regency is categorized as good with a percentage of 97.9%; 2) The satisfaction level of robusta coffee farmers with the performance of PPL in Kemiri Village, Panti Subdistrict, Jember Regency is categorized as satisfied with a percentage of 87.2%; 3) There is a significant relationship between the performance of PPL and the satisfaction of robusta coffee farmers in Kemiri Village, Panti Subdistrict, Jember Regency.